2019
DOI: 10.2147/ott.s188270
|View full text |Cite
|
Sign up to set email alerts
|

<p>Downregulation of KLF13 through DNMT1-mediated hypermethylation promotes glioma cell proliferation and invasion</p>

Abstract: Background Recent evidence indicates that Kruppel-like factor 13 (KLF13) has critical roles in regulating cell differentiation, proliferation and may function as a tumor suppressor. However, its role in glioma progression is poorly understood. Methods Public database was used to explore the expression and prognostic value of KLF13 in glioma. Cell proliferation and invasion assays were used to explore the role of KLF13. Bisulfite sequencing and ChIP assay were used to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 37 publications
2
14
0
Order By: Relevance
“…Nevertheless, the role of miR-125-5p and its mechanism of action in osteosarcoma via zinc-finger transcription factor, Kruppel-like factor 13 (KLF13) are elusive. KLF13 is known for its tumor promotive role and has been shown to affect cell differentiation, proliferation, cell cycle and apoptosis (Wu et al 2019). The present study showed that miR-125 has sufficient downregulation in osteosarcoma and directly targets KLF13 to regulate the growth and viability of osteosarcoma cells.…”
Section: Introductionsupporting
confidence: 53%
“…Nevertheless, the role of miR-125-5p and its mechanism of action in osteosarcoma via zinc-finger transcription factor, Kruppel-like factor 13 (KLF13) are elusive. KLF13 is known for its tumor promotive role and has been shown to affect cell differentiation, proliferation, cell cycle and apoptosis (Wu et al 2019). The present study showed that miR-125 has sufficient downregulation in osteosarcoma and directly targets KLF13 to regulate the growth and viability of osteosarcoma cells.…”
Section: Introductionsupporting
confidence: 53%
“…DNMT1, along with DNMT2, DNMT3A, DNMT3B, and DNMT3L, belongs to DNA methyl transferase family, which regulate target gene expression by the CpG island methylation (Wu et al, 2019). Aberrant methylation, particularly in the promoter regions of tumor suppressor genes, inhibits gene expression and can facilitate human tumorigenesis (Zhou et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…30 DNMT1-mediated KLF13 epigenetic silencing plays a role in regulating glioma cell proliferation and invasion, and the upregulation of KLF13 may be found to be a new treatment. 31 However, the exact function of KLF13 in HCC remains to be explored. Here, we found that KLF13 was a tumor promoter in HCC.…”
Section: Discussionmentioning
confidence: 99%